Study of Erosion Performance and Characterization of Ebonite Reinforced With Carbon Fibers - Debnath, U. K.; Chowdhury, M. A.; Nuruzzaman, D. M. (ASTM International, 2016)
Composite materials have many applications at different mechanisms in industry. The erosion characteristics of new combinations of ebonite reinforced with carbon fiber were analyzed in this study. Randomly-shaped sand (SiO2) particles of various sizes (300–355, 355–500, and 500–600 μm) were selected erosive element. Tested conditions such as impact angles between 15 and 90o, impact velocities between 30 and 50 m/s, and stand-off distances 15–25mm at surrounding room temperature were maintained. The highest level of erosion of the tested composite was obtained at 60o impact angle, which signifies the semi-ductile behavior of this material. Erosion showed an increasing trend with impact velocity and decreasing nature in relation to stand-off distance. Surface damage was analyzed using SEM to examine the nature of the erosive wear mechanism.